Methoxyethyl Etomidate Hydrochloride (ET‐26): A Phase I Clinical Trial Assessing Drug–Drug Interactions in Healthy Subjects - Yang, Fan; Ye, Pan‐Pan; Lv, Wen‐Shuo; Li, Li‐Ze; Zhao, Bao‐Zhong; van denAnker, John; Yang, Xin‐Mei; Song, Lin‐Lin; Yang, Xiao‐Ran; Zheng, Yi; Ke, Bo‐Wen; Zhao, Wei (Journal of clinical pharmacology, 2025)
Methoxyethyl etomidate hydrochloride (ET‐26) is a novel intravenous general anesthetic designed to address the clinical limitations of etomidate. This Phase I clinical trial assessed the pharmacokinetics, pharmacodynamics, drug–drug interaction (DDI) potential, and safety of ET‐26 in 68 healthy subjects across three sequences, evaluating interactions with rifampin (CYP2C19/3A4 inducer), fluconazole (CYP2C19/3A4 inhibitor), and omeprazole/midazolam. ET‐26 pharmacokinetic analyses showed that compared with administration of ET‐26 alone, co‐administration of rifampin resulted in a 10% decrease in the geometric mean ratio (GMR) of the AUC0‐∞ for ET‐26 (GMR 90.0%, 90% CI 85.4%‐94.8%), while co‐administration fluconazole increased the AUC0‐∞ by 18.5% (GMR 118.5%, 90% CI 111.4%‐126.2%). ET‐26 slightly increased the AUC0‐∞ by 18.5% for omeprazole (GMR 118.5%, 90% CI 111.4%‐126.1%) and 11.1% for midazolam (GMR 111.1%, 90% CI 104.9%‐117.8%). The 90% CI for key parameters largely fell within no‐effect boundaries, indicating no clinically significant DDIs. Pharmacodynamic assessments showed consistent sedation profiles across sequences, with mild additive effects with midazolam. Safety evaluations identified treatment‐emergent adverse events such as injection site pain and myoclonus, more frequent with fluconazole. No serious adverse events were observed. These findings suggest ET‐26 exhibits a favorable safety and pharmacokinetic profile with no significant DDIs observed in clinical, supporting its potential as a safer alternative to etomidate for general anesthesia.